Luteal phase support in fresh and frozen embryo transfers - Greenbaum, Shirley; Athavale, Ahlad; Hershko Klement, Anat; Bentov, Yaakov (Frontiers in Reproductive Health, 2022)
Context Luteal phase support (LPS) has become an essential component of IVF protocols following both fresh and frozen embryo transfers, yet there is still controversy with regards to the optimal protocol of LPS to enhance treatment outcome. Search strategy A search via PubMed for all the selected topics was limited to publications from the past 10 years and to English language. We subsequently searched the reference lists of retrieved articles. Where available, RCTs were chosen over non-randomized studies. Here we provide an updated review of the current literature on various issues relating to LPS, in both fresh and frozen embryo transfers. The timing of LPS initiation as well as the route of administration and dosing are discussed for both fresh and frozen transfers. A separate discussion for frozen thawed embryo transfer in natural cycles and non-ovulatory cycles is presented. Conclusions We present data that supports the use of Progesterone LPS in fresh and frozen embryo transfers. No benefits were found to the addition of hCG or estradiol to progesterone LPS in fresh transfers, however GnRH agonist may have a role. IM Progesterone was not advantageous over vaginal progesterone in fresh transfers but was superior in frozen transfers. The timing of LPS introduction, the interval to embryo transfer, as well as the serum concentration of progesterone, have significant effects on the success of the treatment.